1988
DOI: 10.1139/z88-062
|View full text |Cite
|
Sign up to set email alerts
|

Anion-stimulated ATPase in locust rectal epithelium

Abstract: The rectum, the main reabsorptive site in the locust excretory system, actively transports Cl−. This Cl− absorption is electrogenie, not dependent on Na+or [Formula: see text] and insensitive to inhibitors of NaCl cotransport or [Formula: see text] exchange. To determine if active Cl− transport across rectal epithelia might be due to an anion-stimulated ATPase, a microsomal fraction was obtained by differential centrifugation. Microsomal ATPase activity was stimulated in the following sequence: sulphite > b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The role of membrane lipids and their micro-environmental changes at the physical and chemical levels may be responsible for the differential response observed at the level of ATPase activity after treatment with neem extract against the C. medinalis . Membrane ATPase, especially in the intestinal epithelium, assists transport and reabsorption of metabolites and nutrients and also secondary transport of ions and non-electrolytes (Lechleitner and Phillips, 1988; Fogg et al, 1991). Babu et al (1996) showed that the ATPase activity in the gut of H. armigera was significantly decreased, due to toxic effects of azadirachtin.…”
Section: Effect Of Meliaceae Secondary Metabolites On Digestive Enzymmentioning
confidence: 99%
“…The role of membrane lipids and their micro-environmental changes at the physical and chemical levels may be responsible for the differential response observed at the level of ATPase activity after treatment with neem extract against the C. medinalis . Membrane ATPase, especially in the intestinal epithelium, assists transport and reabsorption of metabolites and nutrients and also secondary transport of ions and non-electrolytes (Lechleitner and Phillips, 1988; Fogg et al, 1991). Babu et al (1996) showed that the ATPase activity in the gut of H. armigera was significantly decreased, due to toxic effects of azadirachtin.…”
Section: Effect Of Meliaceae Secondary Metabolites On Digestive Enzymmentioning
confidence: 99%
“…Cl -entry across the apical membrane is active, whereas the net electrochemical gradient across the basal membrane favors passive Cl -exit from the cell. To determine if active Cl -transport across rectal epithelia might be due to an anion-stimulated ATPase, a microsomal fraction was obtained by differential centrifugation (Lechleitner and Phillips, 1988). Microsomal ATPase activity was stimulated in the following sequence: sulphite > bicarbonate > chloride.…”
Section: Function Of CL --Atpasesmentioning
confidence: 99%